2015
DOI: 10.12816/0031227
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potential Oxidative Stress in Egyptian Patients with Acute Zinc Phosphide Poisoning and the Role of Vitamin C

Abstract: Objective: To evaluate potential oxidative stress in patients with acute phosphide poisoning and the effect of vitamin C. Methods:Participants were females and divided into three groups; group I: healthy volunteers group II: healthy volunteers received vitamin C, group III: patients with acute phosphide poisoning received the supportive and symptomatic treatment and group IV: patients with acute phosphide poisoning received the supportive and symptomatic treatment in addition to vitamin C. All the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
5
3
0
Order By: Relevance
“…Regarding the amount of phosphides, 29.3% of studied patients were exposed to unknown amount of phosphides with the majority of ZnP poisoned patients were exposed to one sachet while ALP intoxicated patients were exposed to 0.25-1 tablet. In line with our results, Sagah et al (2015) study reported that ZnP intoxicated patients ingested from 0.25-2 sachets and all of them were asymptomatic. Trakulsrichai et al (2017) found that most of their studied patients were exposed to less than one sachet of ZnP.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Regarding the amount of phosphides, 29.3% of studied patients were exposed to unknown amount of phosphides with the majority of ZnP poisoned patients were exposed to one sachet while ALP intoxicated patients were exposed to 0.25-1 tablet. In line with our results, Sagah et al (2015) study reported that ZnP intoxicated patients ingested from 0.25-2 sachets and all of them were asymptomatic. Trakulsrichai et al (2017) found that most of their studied patients were exposed to less than one sachet of ZnP.…”
Section: Discussionsupporting
confidence: 92%
“…Majority of acute phosphides intoxicated patients were females (63.3%). Our result was supported by other studies, explained by higher liability of female to stress (Mahmoud et al, 2013;Sagah et al, 2015 and. Etemadi-Aleagha et al (2015) and Trakulsrichai et al (2017) are against the current study as they reported that males were more exposed to acute phosphides toxicity than females and explained this by their involvement in various social activities exposing them to more stress.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations